Minimally invasive pain management in chronic musculoskeletal pain: A Community service at Blahkiuh I Health Center - Parami, Pontisomaya; Suranadi, I Wayan; Utara Hartawan, I Gusti Agung Gede; Mahaalit, I Gusti Ngurah; Ryalino, Christopher; Pradhana, Adinda Putra (Bali Journal of Anesthesiology, 2019)
ABSTRACTPain is a common complaint found in the population. Inadequate knowledge about pain management is the most common reason that triggers the inadequate management of pain. Pharmacological pain management is also not without risk. Various risks from the use of pharmacological agents related to side effects that can arise may also cause new problems. Several medical intervention techniques with invasive procedures for pain have also been carried out, although they are still less popular, due to a lack of public knowledge of this technique. We conducted a cost-free, minimally invasive pain procedure in people with chronic musculoskeletal pain in a public health center in a rural area in Bali Island to alleviate their pain-associated symptoms and to introduce this minimally invasive pain management technique.